Embracing the Covenant with Creation: Integral Ecology according to Pope Benedict XVI - Ramage, Matthew J. (Theology and science, 2025)
This essay argues that a genuinely Catholic vision of creation care (integral ecology) is grounded in the often-overlooked truth of humanity's profound unity with all creatures, a unity the Catholic tradition expresses through the idea of a cosmic covenant and the image of creation as a single “organism” or “book.” Drawing on ancient and modern theological sources, especially Joseph Ratzinger, it explores the implications of this vision for human responsibility toward creation and our own kind. Above all, it will be emphasized that respecting the natural order also requires recognizing that “man, too, has a nature that must be respected.”